The Subline of Metastatic Prostate Cancer Cell line, DU145 expresses Tks4 and reveals distinctive Phenotype - Aldhafeeri Hq, Leong Hs (Pakistan Journal of Medical & Health Sciences, 2022)
Cancer metastasis is the process of dissemination of cancer cells from their original site and localization in distant sites. During this journey, metastatic cancer cells have to undergo several phenotypical/ genotypical changes for acquiring cell migration, invasion, attachment properties etc. These steps can be partially/fully mimicked under in vivo and in vitro conditions. Here, we injected metastatic prostate cancer cell line, DU145, into the chorioallantoic membrane )CAM( of the chicken embryo to generate sublines which were isolated 7-days post-injection, and subcultured under in vitro conditions. Our results showed that one of these sublines, DC-1-, exhibited a distinctive phenotype compared with the parental cell line when grown in 3D culture model. Further, the expression of Tks4 at the mRNA and protein level in DC-1- cells was observed to be higher than the regular DU145 cells. Keywords: Prostate cancer, DU145, DC-1-, Metastasis, Round, Stellate, Colony, Tks4